2020
DOI: 10.3126/njb.v8i3.33664
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Actinomycetes from Soil for Antibacterial Activity

Abstract: Actinomycetes are Gram positive, free living saprophytes which are distributed in soil as one of the major populations and are primary source of antibiotics. This study was carried out with a quest to isolate actinomycetes from soil samples of different places and assess their antibacterial activity. Isolation of actinomycetes was carried out by serial dilution of soil sample followed by spread plate method. The antimicrobial extract was extracted using ethyl acetate. Assessment of antimicrobial activity was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
3
18
0
2
Order By: Relevance
“…Therefore, it is an urgent need for searching new, potent, and broad-spectrum antimicrobial agents against infectious pathogens from microbial sources [ 7 ]. Actinomycetes especially Streptomyces have proven potential to produce bioactive compounds and are the richest sources of secondary metabolites including novel antibiotics [ 8 10 ]. Thus, exploration of bioactive metabolite compounds for potential use in biotechnological, agricultural, and biopharmaceutical applications from actinomycetes isolated from unexplored and extreme environments has required considerable attention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is an urgent need for searching new, potent, and broad-spectrum antimicrobial agents against infectious pathogens from microbial sources [ 7 ]. Actinomycetes especially Streptomyces have proven potential to produce bioactive compounds and are the richest sources of secondary metabolites including novel antibiotics [ 8 10 ]. Thus, exploration of bioactive metabolite compounds for potential use in biotechnological, agricultural, and biopharmaceutical applications from actinomycetes isolated from unexplored and extreme environments has required considerable attention.…”
Section: Discussionmentioning
confidence: 99%
“…niger ATCC10535). This indicated that the occurrence of actinomycete isolates with antimicrobial activity in the current research region was higher than 45.3% [ 8 ] and lower than 71.9% [ 12 ]. These relatively high proportions of numbers of isolates from the study area suggest that samples of the Rift Valley of Ethiopia have a high potential for the isolation of actinomycetes having antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the formation of colonies, they were sub-cultured in a test tube containing SCA slants, incubated at 28 °C for 7 days, and then kept in the fridge as the stock. To prevent the cultures from dying out, the isolates were subculture again every 2–3 weeks ( Budhathoki and Shrestha, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The colony of selected actinomycetes that showed the most activity against test organisms in primary screening was cut from their pure culture and placed in the broth. For 8 days, the conical flasks were placed in a rotary shaker incubator at 28 °C ( Budhathoki and Shrestha, 2020 ).…”
Section: Methodsmentioning
confidence: 99%